2014
DOI: 10.4236/ojog.2014.410083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Socio-Demographic Factors Associated with the Satisfaction Related to the Childbirth Experience

Abstract: Assessment of the socio-demographic factors associated with the satisfaction is related to the childbirth experience. Objective: A mother's satisfaction with the childbirth experience may have instant and lasting effects on her wellbeing, and on the bonding with her infant. The main aim of the study was to assess which socio-demographic factors are associated with this satisfaction. Most factors that authors agree on are: Pain intensity, personal control, self-efficacy, length of labor, method of delivery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
9
22
0
Order By: Relevance
“…Although insignificant, postnatal mothers whose age was 25 and above were more likely to be satisfied with delivery service than below 25 (OR = 1.365; CI = 0.462–4.017), and homemakers were more likely to be satisfied than other occupations (OR = 1.807; CI = 0.679–4.810). This finding is consistent with the study done in Lebanon, which showed that patients who are older are more satisfied with the childbirth experience and unemployed mothers were more satisfied with the childbirth experience than employed mothers [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although insignificant, postnatal mothers whose age was 25 and above were more likely to be satisfied with delivery service than below 25 (OR = 1.365; CI = 0.462–4.017), and homemakers were more likely to be satisfied than other occupations (OR = 1.807; CI = 0.679–4.810). This finding is consistent with the study done in Lebanon, which showed that patients who are older are more satisfied with the childbirth experience and unemployed mothers were more satisfied with the childbirth experience than employed mothers [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the findings of the study done in Oromia, showing that respondents who had no higher education were more satisfied than those who had diploma and above [ 16 ]. In contrast to this, the study done in Lebanon showed that women who reached college or more were more satisfied with the childbirth experience than women with an education of high school or less [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported in Serbian public hospitals [34] and Ghana, respectively [32]. Previous studies also found that mothers who experienced their last child birth by normal vaginal delivery were more satisfied [40,41]. On the contrary, in Ethiopia mothers who had gone through natural vaginal delivery were less satisfied with delivery care as compared to mothers who had cesarean section [31].…”
Section: Discussionsupporting
confidence: 82%
“…The women's birth satisfaction was positively associated with age, number of children, education level and income 18 . Those who had more personal control during childbirth 19 , more social support 20 , medical problems during labor 20 and low labor pain 19 showed higher birth satisfaction levels.…”
Section: Introductionmentioning
confidence: 93%